Tyrosinase mediated oxidative functionalization in the synthesis of DOPA-derived peptidomimetics with anti-Parkinson activity. Issue 33 (10th April 2017) - Bizzarri, Bruno M.; Martini, Alessandro; Serafini, Francesco; Aversa, Daniela; Piccinino, Davide; Botta, Lorenzo; Berretta, Nicola; Guatteo, Ezia; Saladino, Raffaele
Abstract : DOPA-derived peptidomimetics are an attractive therapeutic tool for the treatment of Parkinson's disease. Abstract : DOPA-derived peptidomimetics are an attractive therapeutic tool for the treatment of Parkinson's disease. Compounds with unusual O–C and N–C covalent bonds between amino acids have been prepared by selective oxidative functionalization of tyrosine residues with tyrosinase from Agaricus bisporus . The reaction proceeded through a Michael-like nucleophilic addition of amino acids on the DOPA quinone intermediate initially produced by tyrosinase oxidation. The reaction was effective under heterogeneous conditions by immobilization of tyrosinase on multi walled carbon nanotubes (MWCNTs). The anti-Parkinson activity of novel DOPA-derived peptidomimetics was evaluated by electrophysiological techniques on individual dopaminergic neurons in rat ex vivo midbrain slices. Gly- N -C-DOPA and Val- N -C-DOPA-derived peptidomimetics inhibited neuronal firing and evoked outward currents via activation of the D2 receptors in most dopamine-sensitive neurons. In a subset of neurons which displayed low dopamine sensitivity, Gly- N -C-DOPA also caused significative effects.